Vécus croisés de médecins et de patients. Le cas de l’annonce diagnostique de la maladie rare - Séverine Colinet; Céline Avenel (Éducation et Socialisation)
The aim of this paper is to analyze the announcement of a renal fetal disease, this announcement activity being located at the joint between the accompaniment experience of doctors and the "families medical working" (Waissman, 1995). Following an investigation conducted around semi-structured interviews with doctors (32) and couples (30), our results show that resources combining care actions or activities and educational actions or activities reduce the feeling of threat for the patients, and also for the couples during the announcement process. Through the analysis of therapeutic education systems and parental meetings, we discuss not only the need to take into account the changes in the social role of the couple in family parent-caregiver but also the interest of including a collective approach in the announcement accompaniment process.